Spatial distribution of tree and grassland fine roots in an alley cropping system - Sutterlütti, Rahel; König, Isabell; Swieter, Anita; Jansen, Martin (Frontiers in Agronomy, 2023)
Alley cropping systems are known as more sustainable land use alternatives compared to monoculture cropland. In addition to the improvement of above-ground structures and creation of biotopes relevant to nature conservation, the improvement of resource development through various root systems plays a major role. We studied the interaction of the root systems in an alley cropping system combining permanent grassland and willows and at a reference grassland site. The system was established 12 years prior to our study on a site with a shallow groundwater table at 130 cm depth. We measured carbon stocks in the topsoil and determined the share of root-bound carbon relative to the total carbon pool and extracted soil cores up to a depth of 150 cm along a distance gradient to the trees and at a reference grassland site with no tree influence. The maximal rooting depth of the grassland roots increased with increasing distance to the tree lines and total root biomass was higher than under the grassland reference up to a distance of 2.5 m from the tree line. Tree roots extended up to a distance of 5.5 m from the trees and we could distinguish zones of tree root dominance very close to the trees, zones of grassland root dominance at distances ≥ 8.5 m and an interaction zone in between those two extremes. We conclude that alley cropping increases belowground biomass as compared to grassland and has therefore a higher potential to store carbon in the subsoil.